Viabilidade do uso de biota vegetal para caracterização biofísica e análise dosimétrica de danos citogenéticos induzidos por radiação ionizante - Xavier, Magno Nogueira (2023)
It is a consensus within the scientific community the need to broaden the understanding of the biophysics involved in the processes of induction of biological damage caused by low and moderate doses of radiation, both for protection against their undesirable effects and for modulating them for multifaceted applications. The use of higher plants in bioassays is a widely employed tool for the detection and screening of potentially genotoxic agents. Among plant species, onion (Allium cepa) is one of the most used models for determining the genotoxic potential of various chemicals, with effects that were comparable in up to 82% between tests to determine genetic abnormalities carried out with animal models. However, its use for investigating radio-induced toxicity remains insufficiently explored. In this work, Allium cepa roots were irradiated with 241Am and 90Sr/90Y sources, emitting a and B particles, respectively, aiming to quantify the frequencies of major radioinduced cytogenetic endpoints and select the most suitable one for plotting cytogenetic dose-response curves. Computational simulations of the experimental scenarios were performed using Monte Carlo codes to determine the absorbed dose rates by Allium cepa roots. Additionally, for the B irradiations, a TL dose-response curve was plotted for comparison purposes using TLD-100 irradiations with the same experimental setup used for the Allium cepa root irradiations. Parameters such as differences in LET, dose rates, absorbed doses, as well as the influence of different time intervals after irradiation, were considered. The main results include a linear dependence of micronucleus frequency on dose for a particle irradiation, from 0.02 to 0.08 Gy, with cytotoxic activity starting at 0.1 Gy. On the other hand, for B particle irradiations, within the range of 0.04 to 1.44 Gy, the dependence of micronucleus frequencies on doses was nonlinear. Cytotoxic activity was not detected, but an aggravation of genotoxic damage was observed from 0.72 Gy, detected as cells with two and three micronuclei. Analyses of temporal evolution after three cell cycles following irradiations indicated potential for chromosomal instability through micronucleus frequencies. Data on the influences of different absorbed dose rates of B particles (D 1 = 1.4 ± 0.1 mGy/s, D 2 = 5.3 ± 2.3 mGy/s, D 3 = 12.2 ± 3.4 mGy/s e D 4 = 13.9 ± 3.2 mGy/s) while keeping the absorbed dose fixed (0.72 Gy) revealed distinct behaviors in radio-induced micronucleus frequencies, but all influenced by changes in the mitotic index. Following these analyses, a mathematical model was proposed that incorporated a correction factor that approximates the estimated absorbed beta radiation dose detected via micronucleus frequency to the absorbed dose detected via conventional TL dosimetry. This correction factor allowed for subtracting the influence of the quadratic coefficient from the linear coefficient of the dose, based on radiobiological fundamentals. This, in turn, showed that as the dose was increased, the quadratic coefficient exerted greater influence on the dose estimate, mainly due to the possible increase in mutagenic activity. In conclusion, the frequency of micronuclei in Allium cepa cells showed potential for use as a cytogenetic biodosimeter, provided appropriate radiobiological considerations and mathematical adjustments are made.